Demographic Factors and Clinical Presentation of Children under 12 years Admitted With Pneumonia In Benazir Bhutto Hospital Rawalpindi, 2018 - Rai Muhammad Asghar , Rai Rijjal Ashraf , Qurrat-ul-Ann, Rai Muhammad Asghar , Rai Rijjal Ashraf , Qurrat-ul-Ann (Journal of Rawalpindi Medical College, 2019)
Introduction: The spectrum of respiratory illness is quite broad and encompasses diseases of upper and lower airways of both communicable and non-communicable types. Morbidity and mortality caused by lower respiratory tract infections is significantly high in children particularly in those younger than 5 years of age. Among these pneumonias, the most serious illness and can be difficult to diagnose and differentiate from clinically similar conditions due to inadequate radiologic and pathologic methods available, especially in resource poor countries. Objective: The objective of current study is to explore the socio-demography and spectrum of clinical features at presentation of children from birth till 12 years of age, admitted with diagnosis of pneumonia at department of paediatrics BBH, district Rawalpindi. Methods: This paper presented a prospective quantitative case study of community acquired pneumonia at Department of Paediatrics of Benazir Bhutto Hospital Rawalpindi for the year 2018. Applying purposeful/convenience sampling for every admitted case, of under 12 years children with diagnosis of Community acquired pneumonia, the children were subjected to a detailed history and clinical examination. The demographic profile and clinical features of each case were recorded on a study Performa. The data was entered in SPSS 24 and analysed for descriptive statistics. Chi Square test was applied to measure the association between clinical features at presentation. A p-value of less than 0.05 at 95% CI was considered significant. Results: Out of 1287 patients that were admitted with possible diagnosis of pneumonia 60.2% were males while 39.8% were females with a ratio of 1.4:1. Community acquired pneumonia was found to be significantly more common in children of parents having low income levels, a private job and with less education background. Pneumonia was significantly diagnosed more often in infants (1-12m) who made up 72.5% of total sample, (n=933). The commonest symptoms in all age groups were fever and cough, seen in 92.5% and 87% patients respectively. The next most common presenting feature was breathing difficulty in 40% and reluctance to feed/anorexia in 25%of patients. Among the clinical signs, chest in-drawings were observed in 90% and nasal flaring in 37% while crepitation were heard in 53% and wheeze in 9.4 % of cases. Out of 1287 cases, 8.70% children (n=112) died. Among all deaths, 80.3 % (n=90) occurred in the infant age group. Conclusions: Respiratory illness is one of the commonest causes of admission in paediatric wards of a tertiary care hospital. Despite advancement in preventive and management strategies, broncho-pneumonia is still a serious respiratory disease and clinical presentation on admission is strongly related with a high likelihood of diagnosis of pneumonia in low resource settings. Keywords—Demography, Clinical Presentation, Paediatric Pneumonia